Influence of traffic emissions on the carcinogenic polycyclic aromatic hydrocarbons in outdoor breathable particles - Klara Slezakova (2010)
Because polycyclic aromatic hydrocarbons (PAHs) have been proven to be toxic, mutagenic, and/or carcinogenic, there is widespread interest in analyzing and evaluating exposure to PAHs in atmospheric environments influenced by different emission sources. Because traffic emissions are one of the biggest sources of fine particles, more information on carcinogenic PAHs associated with fine particles needs to be provided. Aiming to further understand the impact of traffic particulate matter (PM) on human health, this study evaluated the influence of traffic on PM(10) (PM with aerodynamic diameter <10 mu m) and PM(2.5) (PM with aerodynamic diameter <2.5 mu m), considering their concentrations and compositions in carcinogenic PAHs. Samples were collected at one site influenced by traffic emissions and at one reference site using low-volume samplers. Analysis of PAHs was performed by microwave-assisted extraction combined with liquid chromatography (MAE-LC); 17 PAHs, including 9 carcinogenic ones, were quantified. At the site influenced by traffic emissions, PM,c, and PM2.5 concentrations were, respectively, 380 and 390% higher than at the background site. When influenced by traffic emissions, the total concentration of nine carcinogenic compounds (naphthalene, chrysene, benzo(a)anthracene, benzo(b) fluoranthene, benzo(k)fluoranthene, benzo(a)pyrene, dibenzo(a,h)anthracene, indeno(1,2,3-cd)pyrene, and dibenzo(a,l)pyrene) was increased by 2400 and 3000% in PM(10) and PM(2.5), respectively; these nine carcinogenic compounds represented 68 and 74% of total PAHs for PM(10) and PM(2.5), respectively. All PAHs, including the carcinogenic compounds, were mainly present in fine particles. Considering the strong influence of these fine particles on human health, these conclusions are relevant for the development of strategies to protect public health.